The Relevance of Moral Education from an Islamic Perspective as the Basis for Character Building - Rahma Noviana; Mahima Ayu Dwi Prasetyo; Fathimah Az Zahraa; Ro’ifah (Konsultan Jurnal Ilmiah Indonesia, 2025)
In this fast-paced era of globalization, the formation of individuals with integrity and high moral character has become a major focus in various disciplines. Failure in character education is often linked to an increase in social problems and ethical degradation in society. In Islam, moral education is not only social ethics, but also a manifestation of faith that encompasses vertical and horizontal relationships, making it a major pillar in character building. This study aims to examine in depth the relevance of moral education in the Islamic perspective as an irreplaceable foundation in the character-building process. The focus of the study includes an analysis of basic principles, identification of effective methods of formation in accordance with the Qur'an and Sunnah, and the implementation of moral values in the contemporary education system. The method used is library research, which relies on analysis of various writings and theories from relevant literature (reference books, journal articles, proceedings, and documents). Data is analyzed using content analysis, which includes the stages of problem identification, framework development, methodology, analysis, and data interpretation. Moral education, as conceptualized by Imam Al-Ghazali, is the cultivation of character traits in the soul that result in good deeds coming easily. The methods used to shape this character include direct teaching (the example set by the Prophet Muhammad) and indirect teaching (wisdom stories), as well as early cultivation through the instilling of faith and piety. Moral education is relevant in shaping a character that is not only intellectually intelligent, but also spiritually and emotionally mature, capable of being an agent of positive change, and possessing moral resilience in the midst of globalization. Moral education in Islam is an irreplaceable fundamental foundation in shaping the character of students to be whole (insan kamil), have integrity, and be highly moral. Further research is recommended to empirically examine the implementation of moral education at various levels of education and measure its concrete impact on changes in student behavior.